Transformation of Rhodococcus fascians by High-Voltage Electroporation and Development of R. fascians Cloning Vectors - Desomer, Jan (1990)
The analysis of the virulence determinants of phytopathogenic Rhodococcus fascians has been hampered by the lack of a system for introducing exogenous DNA. We investigated the possibility of genetic transformation of R. fascians by high-voltage electroporation of intact bacterial cells in the presence of plasmid DNA. Electrotransformation in R. fascians D188 resulted in transformation frequencies ranging from 10(5)/μg of DNA to 10(7)/μg of DNA, depending on the DNA concentration. The effects of different electrical parameters and composition of electroporation medium on transformation efficiency are presented. By this transformation method, a cloning vector (pRF28) for R. fascians based on an indigenous 160-kilobase (chloramphenicol and cadmium resistance-encoding) plasmid pRF2 from strain NCPPB 1675 was developed. The origin of replication and the chloramphenicol resistance gene on pRF28 were used to construct cloning vectors that are capable of replication in R. fascians and Escherichia coli. The electroporation method presented was efficient enough to allow detection of the rare integration of replication-deficient pRF28 derivatives in the R. fascians D188 genome via either homologous or illegitimate recombination.